Religious Moderation in Addressing Qibla Direction Deviation: A Case Study of Al-Munawwar Grand Mosque in Tulungagung, Indonesia - Ahmad Musonnif; Muhammad Mufti al Anam; Muhammad Rizki Syaifudin Irsyad; Mohammad Amirudin (Al-Hilal: Journal of Islamic Astronomy, 2026)
The qibla direction is a fundamental requirement in Islamic prayer, yet its misalignment often generates debate at the community level. The Al-Munawwar Grand Mosque in Tulungagung, Indonesia, exhibits a deviation of approximately 30°, leading to differing responses among religious leaders, Islamic organizations, and government institutions. Previous studies have largely focused on technical-astronomical accuracy or social conflict, while limited attention has been given to the role of religious moderation in managing such disputes. This study aims to analyze stakeholders’ responses to qibla deviation and to formulate resolution strategies grounded in religious moderation. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis. Thematic analysis reveals three dominant orientations: rigid groups demanding absolute precision, moderate groups advocating gradual adjustment through deliberation, and tolerant groups emphasizing the sufficiency of jihat al-ka’bah. The findings suggest that integrating religious moderation with modern astronomical technology provides an effective framework for resolving qibla disputes, preserving worship validity, and sustaining congregational harmony.